International organizations and civilian protection : power, ideas and humanitarian aid in conflict zones - Chaulia, Sreeram (The library of international relations, 2012)
Despite the proliferation of international humanitarian and human rights laws since the end of the Cold War, there has been an erosion of the practical immunity of civilians caught up in armed conflicts. This title explores the attempts of international humanitarian organizations to relieve the plight of these civilians